As herbáceas Sesuvium portulacastrum (Aizoacea) e Batis maritima (Batacea) facilitam o estabelecimento e crescimento de Avicennia germinans (Acanthaceae) em um manguezal em recuperação na Apa do estuário do rio Pacoti, Ceará, Brasil - Villavicencio, Carolina Bracho (2020)
In restoration ecology, the role played by pioneering halophytes in facilitating the mangrove life cycle is little studied, being an important theme in the recovery of these ecosystems. This study aims to evaluate density and growth patterns of Avicennia germinans associated with the presence of B. maritima and S. portulacastrum as possible facilitators. 15 plots of 4 m2 were randomly established, with 5 plots in one spot for each species of facilitator and 5 in an adjacent control area. Individuals of A. germinans were counted in each plot monthly, from Dec / 2017 to Nov / 2019. Individuals were also tagged with serial seals to be measured monthly in each plot. The height was measured with a tape measure, from the soil to the apical bud in plants greater than 15 cm in height, from Feb / 2019 to Nov / 2019. The growth rate was calculated by subtracting the final height (Hf) from the initial height (Hi) and dividing by the number of days sampled (d). Salinity, temperature and sediment samples were analyzed to associate them as environmental parameters. The density of A. germinans was always higher in the S. portulacastrum spot with 14.89 ± 7.41 ind / m2 (mean ± dev.p), followed by B. maritima with 10.56 ± 6.12 ind / m2 and Control with 5.43 ± 3.17 ind / m2, varying significantly between them (p <0.05). The growth rate was always lower in S. portulacastrum with 2.30 ± 2.70 cm / month (mean ± deviation), 3.82 ± 4.36 cm / month in Control and higher in B. maritima with 4 , 66 ± 3.91 cm / month. These results describe an inversely proportional relationship between A. germinans density and growth between treatments. The month factor was the one that best explained the data trends in the model of relationship between densities and growth rates adjusted to log10, resulting in a greater proportion of positive trends in S. portulacastrum and B. maritima when compared to Control. Once these pioneer plants change the physical conditions of the site, They facilitate A. germinans on different aspects: B. maritima and promotes their growth and S. portulacastrum promotes its establishment, as proved density-dependent positive trends on rates adjusted growth rates associated with the studied facilitating plants.